The Use of Classical and Modern Arabic Short Stories as a Strategy for Improving Arabic Language Skills - Perdana, Dyah Adila (Journal of Arabic Language Studies and Teaching, 2026)
This study aims to analyze the use of classical and modern Arabic short stories as a strategy for enhancing Arabic language skills. The study is grounded in the importance of learners’ mastery of formal Arabic (fuṣḥā), communicative competence, and understanding of Arab culture. Classical short stories, such as Maqāmāt al-Ḥarīrī, offer a high level of formal language, complex sentence structures, and challenging rhetorical features, while modern short stories, such as those by Najīb Maḥfūẓ, emphasize communicative language, clear narrative structures, and socio-psychological themes relevant to contemporary life. This article employs a literature review and pedagogical analysis to identify the potential of each type of short story in developing the four Arabic language skills: listening, reading, speaking, and writing. The findings indicate that integrating classical and modern short stories enables the holistic development of Arabic language skills while fostering learners’ motivation, creativity, analytical ability, and cultural understanding. The proposed integrative strategy includes staged learning, textual analysis, communicative practice, written production, and project-based holistic assessment. This article offers a practical contribution for Arabic language teachers in designing effective, contextual, and literature-based instruction.